Facebook Use and Mental Health: Gender and Academic Year Variations in Symptoms - Jehad Feras AlSamhori; Alameen Alsabbah; Lama Sami Mahafzah; Abdel Rahman Feras AlSamhori; Ahmad Feras AlSamhori (University Library System, University of Pittsburgh, 2023)
BACKGROUND: In an increasingly digital age, social media, particularly Facebook, has become an integral part of college students' lives. This study seeks to explore how gender and academic year may influence Facebook addiction and its impact on mental health among this demographic. METHODS: A cross-sectional study was conducted. The survey includes sociodemographic questions and BFAS, GAD-7, and BFAS scales. Data analysis was conducted by SPSS, with statistical tests conducted at a 95% confidence level. Normal distribution was tested with Kolmogorov-Smirnov test. Sperman's correlation was conducted to assess any potential correlation and the Mann-Whitney test was used to investigate any significant differences in the mean score. RESULTS: This study included 1,098 college students aged 18 to 25 (mean age 21.35). A majority (62.8%) of the participants identified as female, and notably, 61.5% were clinical medical students. The Bergen Facebook Addiction Scale (BFAS) was utilized yielding a mean score of (mean: 16.43, SD: 5.934).. Interestingly, most participants reported "Rarely" or "Very Rarely" feeling restless or troubled when unable to use Facebook (64.5%). The Generalized Anxiety Disorder Questionnaire (GAD-7) unveiled that participant experienced mild anxiety, with a mean score of 8.63 (SD: 4.928). Approximately 43.2% reported mild anxiety. Depression, assessed using the Patient Health Questionnaire-9 (PHQ-9), reflected moderate depression with a mean score of 11.70 (SD: 6.39). Correlations were explored among BFAS, GAD-7, and PHQ-9 scores. A strong positive correlation emerged between GAD-7 and PHQ-9 (r: 0.634, p-value < 0.001). Furthermore, there was a significantly moderate positive correlation between BFAS and PHQ-9 (r: 0.344, p-value < 0.001) and a significantly small positive correlation between BFAS and GAD-7 (r: 0.282, p-value < 0.001). The Mann-Whitney Test was employed to investigate gender and academic year differences in scores. Female participants exhibited significantly higher scores than males in BFAS (p-value = 0.028), GAD-7 (p-value < 0.001), and PHQ-9 (p-value = 0.004). Additionally, preclinical students reported higher scores than clinical students in BFAS (p-value < 0.001) and PHQ-9 (p-value < 0.001). CONCLUSION: In summary, this study sheds light on the complex interplay between Facebook use, mental health symptoms, gender, and academic year among college students. It reveals a moderate level of Facebook addiction and varying degrees of anxiety and depression. Gender disparities are evident, with females reporting more severe symptoms. Furthermore, academic year impacts these factors, with preclinical students exhibiting higher scores. Understanding these dynamics is crucial for tailoring interventions and support mechanisms to address the unique challenges faced by college students in the digital age.